PROMOTION AND PRECIOUS PAPERS MARKET (Spectrum Journal of Innovation, Reforms and Development, 2024)
This article analyzes the development of the stock and securities market of Uzbekistan, the current state and prospects of the market. The results of the research show the main indicators of the stock market and their place in the economy. Factors hindering the development of the stock market and ways to overcome them are also considered.